2015
DOI: 10.1785/0220150169
|View full text |Cite
|
Sign up to set email alerts
|

The Central United States Seismic Observatory: Site Characterization, Instrumentation, and Recordings

Abstract: A borehole that penetrated 585 m of soil deposits and terminated 9 m into Paleozoic bedrock was completed near the New Madrid Seismic Zone of the central United States. A vertical array of strongmotion accelerometers and broadband seismometers-the Central United States Seismic Observatory (CUSSO) was installed. CUSSO provides a test site for verification and calibration of seismic-wave propagation analysis and near-surface seismic exploration. Preliminary results show that velocity models produced from the P-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…During the 1976 Tangshan earthquake [1], the seismic damage of two areas in Tianjin was quite different. e survey results showed that the site of the area suffering lighter damage consisted of a soft intercalation of mucky clay at a depth of approximately 10 m. In particular, the earthquake that occurred in Mexico on 19 September 1985 further demonstrated that site conditions have a significant impact on earthquake damage [8]. During this earthquake, Mexico City, which was 400 km away from the epicentre, suffered severe damage, far exceeding the damage that occurred in the area around the city.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…During the 1976 Tangshan earthquake [1], the seismic damage of two areas in Tianjin was quite different. e survey results showed that the site of the area suffering lighter damage consisted of a soft intercalation of mucky clay at a depth of approximately 10 m. In particular, the earthquake that occurred in Mexico on 19 September 1985 further demonstrated that site conditions have a significant impact on earthquake damage [8]. During this earthquake, Mexico City, which was 400 km away from the epicentre, suffered severe damage, far exceeding the damage that occurred in the area around the city.…”
Section: Introductionmentioning
confidence: 98%
“…Existing studies [10,[15][16][17][18] have shown that the impact of site conditions on seismic damage is due to their significant ground motion amplification or deamplification effect. e influence of the nearsurface soil layer on seismic effects has attracted a lot of research due to its widespread impact and the large number of sites involved, and the research studies focused on the formation age [6,7,[19][20][21], genetic type [22][23][24][25], thickness variability [26][27][28], structure [29][30][31][32][33][34], and dynamic characteristics of overlying soil layers [35][36][37][38][39]. Although many studies on site effects have been performed at home and abroad and the results are remarkable, there are few studies of the influence of hard interlayers on the site seismic response.…”
Section: Introductionmentioning
confidence: 99%
“…Both the empirical site response amplification functions and those derived by 1D modeling are frequency dependent. For example, the borehole transfer function, S-wave HVSR, and 1D theoretical transfer function from the CUSSO vertical seismic array (Woolery et al, 2016), upper Mississippi Embayment, shown in Figure 1 all have peaks and troughs. These peaks and troughs, which correspond with SH-wave resonance modes (Boore, 2013), demonstrate that S-wave resonance controls the site response at this site, although the peaks are manifested slightly differently in the various spectral ratios.…”
Section: Introductionmentioning
confidence: 99%